2006
DOI: 10.1021/jp065075p
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Effect on the Photochemical Properties of Symmetrically Substituted trans-3,3‘,5,5‘-Tetramethoxystilbene

Abstract: Photochemical properties of trans-3,3',5,5'-tetramethoxystilbene (TMST) have been studied in various polar solvents. The Stokes shift of trans-TMST was found to be increased with increasing solvent polarity. The fluorescence lifetime of trans-TMST experienced a large solvent effect changing from 2.3 ns in cyclohexane to 16.6 ns in acetonitrile. These results indicate that the excited singlet state of trans-TMST has a charge-transfer (CT) character. On the basis of the obtained results, the interior polar envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Furthermore, the dipole moment in the excited state (® e =9.5 D) is larger than that in the ground state (® g = 2.5 D). 15 It should be noted here that the observed lifetime of 23 ns is the longest one in simply substituted stilbenes. 6 ] are ascribable to the existence of two different solvation environments as shown in Figure 6.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Furthermore, the dipole moment in the excited state (® e =9.5 D) is larger than that in the ground state (® g = 2.5 D). 15 It should be noted here that the observed lifetime of 23 ns is the longest one in simply substituted stilbenes. 6 ] are ascribable to the existence of two different solvation environments as shown in Figure 6.…”
mentioning
confidence: 75%
“…We have found that trans-TMST has considerably long fluorescence lifetime of more than 10 ns in polar solvent such as acetonitrile and decreases with decreasing polarity of the solvent. 15 Thus, TMST was thought to be an appropriate compound to study the real viscosity of ionic liquid and the polarity of ionic liquid from the point of view of microviscosity and bulk viscosity. The measured viscosity of ionic liquid [bmim][PF 6 ] (260 cP) 16 used in these experiments as a solvent is much higher than that of acetonitrile (0.34 cP), 16 18 but is almost equivalent with the value of methanol (55.0).…”
mentioning
confidence: 99%
“…Besides porphyrins and phthalocyanines, there exist a few other types of fluorophores that can be used as the core of water‐soluble dendrimers. The fluorescence in water of the stilbene derivatives 7‐G n (Figure 4) was shown to be blue‐shifted with increasing generations ( λ em =424, 411, and 389 nm for 7‐G 0 , 7‐G 1 , and 7‐G 2 , respectively), indicating the decrease of the interaction between water and the excited state of stilbene, for higher generations 36. The symmetrically substituted perylene 8‐G n (Figure 4) has low fluorescence intensity in water, due to aggregation phenomena that depend on the overall steric requirements of the attached dendritic wedges and on hydrophobic interactions.…”
Section: Fluorescent Cores Of Dendrimersmentioning
confidence: 99%
“…This data indicated that the excited singlet state of trans-TMST has a charge transfer (CT) character. Fluorescence lifetimes of trans-TMST were measured [87]. Effect of solvent polarity on photoisomerization of trans-4,4 0 -bis (benzoxazolyl) stilbene has been reported [86].…”
Section: Viscosity Effectmentioning
confidence: 99%